2021
DOI: 10.7860/jcdr/2021/46566.14556
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic and Morphometric Study of Human Acetabulum and its Clinical Significance

Abstract: Introduction: The acetabulum is a cup shaped hemispherical depression which is present on the hip bone, contributed by ilium, ischium and pubis. It has a central depressed non-articular part called acetabular fossa, surrounded by a curved lunate articular surface which articulates with the head of femur to form hip joint. The knowledge of acetabular dimensions assists the radiologists in diagnosing acetabular dysplasia and aids the surgeon to determine the correct size of the acetabular cup during total hip ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In addition, a very strong positive statistically significant correlation was obtained between LH and IH (r: 0.853, p<0.001) and ADA and VDA (r: 0.881, p<0.001) measurements. [10,11,[15][16][17][18] Upon the examination of radiological images of Chinese adults, Zeng et al found the mean MDA value to be 19.3 mm on the right and 19.4 mm on the left in male and 17.3 mm on the right and 17.4 mm on the left in female. [19] In a study conducted by Indurjeeth et al on the dry hip bones of the Black African population of South Africa, mean VDA, MDA, and LLAN values were found to be 54.84 mm, 31.30 mm, and 21.72 mm, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, a very strong positive statistically significant correlation was obtained between LH and IH (r: 0.853, p<0.001) and ADA and VDA (r: 0.881, p<0.001) measurements. [10,11,[15][16][17][18] Upon the examination of radiological images of Chinese adults, Zeng et al found the mean MDA value to be 19.3 mm on the right and 19.4 mm on the left in male and 17.3 mm on the right and 17.4 mm on the left in female. [19] In a study conducted by Indurjeeth et al on the dry hip bones of the Black African population of South Africa, mean VDA, MDA, and LLAN values were found to be 54.84 mm, 31.30 mm, and 21.72 mm, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have been carried out to determine these parameters to assist Orthopedic Surgeons and Biomedical Engineers in development of suitable hip joint prostheses. 16 Also these measurements are different in different individuals and in various population groups. 17 Abnormalities develop in biomechanics of hip due to the anomalies in acetabular parameters such as, depth, width and diameter resulting in dysplasia of hip, which in turn leads to instability of the hip joint, causing enhanced degeneration of the articular cartilage and ultimately ending in osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have been carried out to determine these parameters to assist Orthopedic Surgeons and Biomedical Engineers in development of suitable hip joint prostheses. 16 Also these measurements are different in different individuals and in various population groups. 17…”
Section: Discussionmentioning
confidence: 99%
“…The articulating surface is termed the lunate. The body weight is transferred to the femur through the lunate, which has its broadest surface just above the point of weight bearing (2) .…”
Section: Introductionmentioning
confidence: 99%
“…The rim of the acetabulum is a ridge formed by the ilium, the ischium, and the pubis. The articular, or hip joint-forming, portion of this opening is termed the lunate surface, and the non-articular, or acetabular, fossa portion is called the acetabular fossa and is covered by a fatty pad (2) . Inferiorly (at the acetabular notch), the articular portion of the acetabular cavity is incomplete, with a sharp tip at its anterior end and a semilunar form at its posterior end.…”
Section: Introductionmentioning
confidence: 99%